Perancangan dan Implementasi Sistem Informasi Akuntansi Kas Kecil Berbasis Web Pada PT. Jasa Marga Jalan Layang Cikampek - Rina Fitriani; Imas Imas; Satria Satria; Ishak Husin (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study aims to design and implement a web-based accounting information system for petty cash at PT. Jasa Marga Jalan layang Cikampek in order to improve efficiency and accuracy in managing petty cash transactions. The problem faced by the company is that petty cash recording is still conducted manually, which leads to potential errors, loss of transaction evidence, and delays in report preparation. This research applies a descriptive approach with data collection techniques including observation, interviews, and documentation. The system is developed using the CodeIgniter framework, designed with Unified Modeling Language (UML), and supported by a MySQL database. The results show that the developed system simplifies the recording process of cash inflows and outflows, enhances data accuracy, and produces financial reports more quickly and systematically. In addition, the system supports internal control through integrated and well-documented data management. Therefore, the implementation of a web-based accounting information system for petty cash provides an effective solution to improve the performance of petty cash management within the company.